Development of levofloxacin glycosylated mesoporous silica nanoparticles for urinary tract infections - Songhita Mukhopadhyay, Reema Narayan, Shivaprasad Gadag, Padmaja A. Shenoy, Sanjay Garg, Ashwini T., Usha Y. Nayak (Journal of Applied Pharmaceutical Science, 2024)
Nanoparticle drug delivery for infectious disease has paved the way for effective treatment; mesoporous silica nanoparticles (MSNs) with versatile design options, tunable pore size, high surface area, and adequate pore volume have garnered widespread interest. The current study deals with the synthesis of MSNs loaded with levofloxacin (LVF), followed by glycosylation to enhance the uptake by bacterial cells. The MSNs were prepared by modifying Stober’s process. The amino-modified MSNs were glycosylated using D-Glucuronic acid by EDAC-NHS coupling chemistry. The LVF -loaded glycosylated MSNs (GLY-MSN) were characterized for various parameters and in vitro antimicrobial efficacy study. The surface functionalized MSNs had a particle size of 673.6 ± 60.81nm and were found to be spherical from the SEM images. The drug loading capacity for plain MSNs and GLY-MSN was found to be 10.41% ± 0.81% and 11.43% ± 0.93%, respectively. The LVF release from GLY-MSN was found to be 21.02% ± 3.38% whereas that from plain MSN was 7.50% ± 1.31% at the end of 48 hours. The minimum inhibitory concentration of LVF-GLY-MSN on Escherichia coli was found to be lesser than that for LVF and LVF-MSN. Hence, the synthesized GLY-MSN may be an effective drug delivery system for the treatment of drug-resistant bacterial infections.
Keywords: Antimicrobial resistance, Levofloxacin, D-Glucuronic acid, Glycosylation, Lectin, Nanoparticle